Identification and in silico structural analysis of Gallus gallus protein arginine methyltransferase 4 (PRMT4). Issue 12 (10th October 2017) - Berberich, Hannah; Terwesten, Felix; Rakow, Sinja; Sahu, Peeyush; Bouchard, Caroline; Meixner, Marion; Philipsen, Sjaak; Kolb, Peter; Bauer, Uta‐Maria
Abstract : Protein arginine methyltransferase 4 (PRMT4) is an essential epigenetic regulator of fundamental and conserved processes during vertebrate development, such as pluripotency and differentiation. Surprisingly, PRMT4 homologs have been identified in nearly all vertebrate classes except the avian genome. This raises the possibility that in birds PRMT4 functions are taken over by other PRMT family members. Here, we reveal the existence of a bona fide PRMT4 homolog in the chicken, Gallus gallus . Using a biochemical approach, we initially purified a putative chicken PRMT4 protein and thus provided the first evidence for the presence of an endogenous PRMT4‐specific enzymatic activity toward histone H3 arginine 17 (H3R17) in avian cells. We then isolated a G. gallus PRMT4 (gg PRMT4 ) transcript encompassing the complete open reading frame. Recombinant ggPRMT4 possesses intrinsic methyltransferase activity toward H3R17. CRISPR/Cas9‐mediated deletion of gg PRMT4 demonstrated that the transcript identified here encodes avian PRMT4. Combining protein–protein docking and homology modeling based on published crystal structures of murine PRMT4, we found a strong structural similarity of the catalytic core domain between chicken and mammalian PRMT4. Strikingly, in silico structural comparison of the N‐terminal Pleckstrin homology (PH) domain of avian and murine PRMT4 identified strictly conserved amino acids that are involved in an interaction interface toward the catalytic core domain, facilitating for the first time a prediction of the relative spatial arrangement of these two domains. Our novel findings are particularly exciting in light of the essential function of the PH domain in substrate recognition and methylation by PRMT4. Abstract : PRMT4 was reported not to exist in the avian lineage. Here, we identify a bona fide PRMT4 homolog, which possesses the same substrate specificity as mammalian PRMT4 and shows a high structural similarity to murine PRMT4. Strictly conserved amino acids predict the relative spatial arrangement of the Pleckstrin homology domain, thereby establishing the structural basis for its essential catalytic function.